2017
DOI: 10.4000/pratiques.3313
|View full text |Cite
|
Sign up to set email alerts
|

La conscience métapragmatique et l’attitude métacognitive épistémique des scripteurs universitaires : la révision de texte en temps réel

Abstract: PratiquesLinguistique, littérature, didactique 173-174 | 2017Le déjà-là dans l'écriture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…We suggest that in class 2, it was the rewriting that allowed these two significant improvements, since the work done by the teacher was not directly related to production of the desired text. Research by Olive and Piolat (2003), Mutta (2017) and Colognesi & Lucchini (2018a) has shown that rewriting on its own can support enrichment of the text by adding ideas and making surface (sentence-centered) improvements. Our result also reinforces the fact that doing activities without giving the students specific objectives, and without informing them of the links they have with the current writing project, is not very effective (Graham et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that in class 2, it was the rewriting that allowed these two significant improvements, since the work done by the teacher was not directly related to production of the desired text. Research by Olive and Piolat (2003), Mutta (2017) and Colognesi & Lucchini (2018a) has shown that rewriting on its own can support enrichment of the text by adding ideas and making surface (sentence-centered) improvements. Our result also reinforces the fact that doing activities without giving the students specific objectives, and without informing them of the links they have with the current writing project, is not very effective (Graham et al, 2012).…”
Section: Discussionmentioning
confidence: 99%